The Emotional Student Well-Being Among Low-income Families in Indonesian Elementary Schools - Muhamad Ahyar Rasidi; Muammar; Nurshahira Ibrahim (Golden Age and Inclusive Education, 2025)
This research is motivated by the emotional well-being of students, which is an essential aspect of education that influences not only academic achievement but also children's personal and social development. This study aims (1) to describe the influence on the emotional well-being of elementary school students from low-income families in Malaysia and Indonesia; and (2) to analyse the factors that influence the emotional well-being of elementary school students from low-income families in Malaysia and Indonesia. This research is qualitative. The researcher's presence is the primary or essential instrument in this research. This research was conducted in two countries, namely Malaysia and Indonesia. The data sources for this research are elementary school teachers and students in the two countries. The data collection methods used were observation, interviews, and documentation. The data analysis methods are acquisition, condensing, presentation, and conclusion drawing/verification. Data validity testing is done through internal and external validity, reliability, and objectivity. The research results show that (1) family conditions influence students' emotional well-being because they include self-awareness, self-regulation, feelings of empathy, motivation, and social skills; and (2) factors that influence students' emotional well-being include individual, environmental (home, school and community), socioeconomic and cultural factors